Band electron spectrum and optical properties of KDP-crystals under the external hydrostatic pressure - Stetsiv, R.Ya. (Condensed Matter Physics, 1999)
The electron spectrum of the KDP-type crystals has been investigated as a function of the external hydrostatic pressure using the tight-binding approximation. The joint density of electron states, real and imaginary parts of the dielectric permeability, refraction indices, the gyration coefficient, absorption and reflection coefficients for different polarizations of light are determined. Their pressure and frequency dependencies are investigated. The results are discussed by comparing them with the experimental data on piezooptic coefficients. The anomalous behaviour of the optical constants at the pressure p ~≃ 17 kbar is due to the transformation of the hydrogen bond potential from a double minimum one to a single minimum one, where the proton is localised at the midpoint of the hydrogen bond.